Breeding Fulvous Whistling-Ducks and other notes on the birds of Querétaro"™s reservoirs - Hiley, Jonathan (Huitzil Revista Mexicana de Ornitología, 2013)
I present a noteworthy breeding record for the state of Querétaro in central Mexico. In addition, I demonstrate records of six species which have not previously been documented in the state. All were seen on a series of reservoirs in the lower half of the state. These further additions to the Querétaro avifauna confirm the importance of these water bodies to a wide range of species.